Completing Banking Union? The Role of National Deposit Guarantee Schemes in Shifting Member States' Preferences on the European Deposit Insurance Scheme - Mario Tümmler (JCMS: Journal of Common Market Studies, 2022)
The gridlock on the European deposit insurance scheme (EDIS), the missing pillar of the banking union, is most commonly attributed to moral hazard concerns on the side of Germany. However, Member State preferences on EDIS cannot be understood solely based on concerns over pre-emptive risk reduction. Instead, banking sector interests connected to the institutional setup and legal status of national deposit guarantee schemes (DGSs) have also informed these preferences. This article examines the development of preference formation on EDIS for the cases of Germany, Italy and France after the initial 2015 proposal failed. National preferences on the institutional setup of EDIS have become more aligned with a reinsurance system that maintains existing DGS. Hence, current trajectories point to a discussion over how national DGSs are to be linked in a reinsurance system, instead of a discussion about whether it should be abandoned or not.
Keywords: 330; banking union; European deposit insurance scheme (EDIS); financial integration; preference formation; eurozone